Practical electronics handbook - Sinclair, Ian Robertson (Elsevier/Newnes, 2007)
Ian Sinclair's Practical Electronics Handbook combines a wealth of useful day-to-day electronics information, concise explanations and practical guidance in this essential companion to anyone involved in electronics design and construction. The compact collection of key data, fundamental principles and circuit design basics provides an ideal reference for a wide range of students, enthusiasts, technicians and practitioners of electronics who have progressed beyond the basics.